Effect of dopants on the nonlinear optical properties of fluorotellurite glasses for optical limiting application. (13th August 2021) - Vani, P; Vinitha, G; Manikandan, N
Abstract: Investigation on non-linear optical property of zinc and barium based fluorotellurite glasses based on open aperture Z-scan technique and its application as an optical limiter is reported. Changes in various parameters like polarizability, refractive index and molar refractivity have been attributed to the presence of barium/ zinc atoms and their impact on modifying the structure. Formation of non-bridging sites owing to fluorine doping have been explored based on Raman measurements. Open aperture data shows reverse saturable absorption behaviour and is attributed to the two-photon absorption process. Non-linear absorption values are found to increase with doping of both barium fluoride and zinc fluoride which has been attributed to the formation of non-bridging fluorine sites alongwith the polarizability of barium atoms. Effect of non-bridging fluorine sites on modifying the optical properties have been justified based on the energy bandgap values. Samples show comparably good optical limiting thresholds with a value of 2.59 × 10 12 W m −2 for the sample with highest fluorine concentration, which enables them to be used as limiting devices.